Reproduction in the bushmaster (Lachesis muta): Uterine muscular coiling and female sperm storage - Souza, Eletra de [UNESP]; Almeida-Santos, Selma Maria [UNESP] (Wiley-Blackwell, 2020)
Prolonged sperm storage in the female reproductive tract is a widespread strategy among vertebrates. In reptiles, especially lizards and snakes, females have specialized structures to store sperm in their oviduct, which occur in the posterior infundibulum and the nonglandular uterus. Many viperids exhibit uterine muscular coiling (UMC) in the nonglandular uterus, and this modification has been proposed as an ancestral trait in this taxon to store sperm. However, UMC and oviductal sperm storage have not been reported in Lachesis. Here, we studied the reproductive tract of L. muta females using histological techniques and describe, for the first time, the occurrence of oviductal sperm storage and UMC in nonglandular uterus of this species. We also describe an increase in secretory activity in the oviduct throughout the reproductive cycle. Our results support the hypothesis that UMC is an ancestral character in Viperidae and suggest that female L. muta must store sperm in the oviduct to fertilize the oocytes. We also propose new hypotheses for reproductive strategies of L. muta in nature.
Keywords: reproductive biology; uterine coiling; Viperidae; vitellogenesis